Magnetic and Multifunctional Magnetic Nanoparticles in Nanomedicine: Challenges and Trends in Synthesis and Surface Engineering for Diagnostic and Therapy Applications - Varanda, Laudemir Carlos; Júnior, Miguel Jafelicci; Júnior, Watson Beck (IntechOpen, 2011)
None